Model-Model Pendidikan Karakter di Sekolah - Hasanah, Uswatun (Universitas Islam Negeri Raden Intan Lampung, 2016)
Currently, there is no doubt that the emergence of various social phenomena is very worrying in many cases form; violence and unrest and moral decadence that befell this nation. The character of the young generation is already at an alarming point. The morality of this nation has been separated from the norm, ethical, religious and noble culture. Damage to morale among students and youth. It is characterized by the rise of casual sex, drug abuse, trafficking in photos and porn video, and fights among students and youth.Based on the results of research conducted by the Institute for the Study of Love and Humanity as well as Business Training and Humanities (LSCK PUSBIH), involving 1,666 respondents in large cities, for example; Medan, Jakarta, Bandung, Yogyakarta, and Surabaya. Teen respondents claimed to have free sex is very high, even exceeding 50%. In addition, according to the Centers for Disease Control Jakarta Social Disorder, elementary school, junior high and high school, which involved brawl reached 0.8%, or approximately 1,318 students (1,645,835), as well as victims of drugs 3.9%. And, even more surprising, for the city of Yogyakarta, about 97.05%, free sex. The facts demonstrate how ironic condition of today's teenagers.Here, the importance of character education in schools internalization intensively by example, wisdom, and unity both intra and extra-curricular programs, as a solid foundation that will benefit future students. Character development is largely forgotten by the school, has been too fascinated with academic targets, dianak favoring the intellectual, emotional and spiritual intelligence while marginalized. It can be concluded that the character of the values of human behavior associated with the Almighty God, ourselves, our fellow human beings, the environment, and nationality embodied in thoughts, attitudes, feelings, words, and actions based on religious norms, laws, etiquette, culture, and customs.